Poor People's Knowledge : Helping Poor People to Earn from Their Knowledge - Finger, J. Michael (World Bank, Washington, DC, 2013)
How can we help poor people to earn more from their knowledge rather than from their sweat and muscle? This paper draws lessons from projects intended to promote and protect the innovation, knowledge, and creative skills of poor people in poor countries, particularly to improve the earnings of poor people from such knowledge and skills. The international community has paid considerable attention to problems associated with intellectual property that poor countries buy-such as the increased cost of pharmaceuticals brought on by the WTO's agreement on the Trade Related Aspects of Intellectual Property (TRIPS). This paper is about the other half of the development-intellectual property link. It is about the knowledge poor people own, create, and sell rather than about what they buy. The paper calls attention to a broad range of poor people's knowledge that has commercial potential. It highlights the incentives for and concerns of poor people-which may be different from those of corporate research, northern nongovernmental organizations, or even entertainment stars from developing countries who already enjoy an international audience. The studies find that increased earnings is sometimes a matter of poor people acquiring commercial skills. Legal reform, though often necessary, is frequently not sufficient. Moreover, the paper concludes that the need for novel legal approaches to protect traditional knowledge has been overemphasized. Standard instruments such as patents and copyrights are often effective. Rather than legal innovation, there is a need for economic and political empowerment of poor people so that they have the skills to use such instruments and the influence to insist that institutional structures respond to their interests. Finally, the paper concludes that there is minimal conflict between culture and commerce. There are many income-earning expressions of culture, and it is incorrect to presume that expressions of culture must always be income-using.